Outcome of sepsis in pediatric oncology patients admitted in pediatric intensive care unit: A developing country perspective - Amna Afzal Saeed; Sadia Usman; Zehra Fadoo; Qalab Abbas (Elsevier, 2019)
Objective: To determine the outcome of sepsis i.e. severe sepsis and septic shock in pediatric oncology patients admitted in pediatric intensive care unit (PICU). Methods: Retrospective review of medical records of all children (1 month-16 years) having primary oncological diagnosis admitted in PICU with sepsis from January 2008 to June 2017 was done after ethical review committee approval. Data was collected on a structured proforma and included demographic details, clinical and laboratory/microbiological data and stage of chemotherapy, outcome (survived/expired). Results: Total 63 patients were identified, 42 (66.7%) were males, and median age was 93 months. Primary oncological diagnosis included Leukemia (n = 45, 71.4%), lymphoma (n = 12, 19.0%), solid tumor (n = 3, 4.2%), central nervous system tumor (n = 2, 3.2%) Out of the 63 admissions, 34.9% (n = 22) went into septic shock and 52.4% (n = 33) survived after admission to PICU. The most commonly found microbial organisms were gram positive cocci, followed by gram negative rods. Organ dysfunction, use of mechanical ventilation and septic shock were associated with mortality (p < 0.05). Conclusion: Sepsis in patients with primary oncological diagnosis carries very high mortality. Gram positive cocci were the most common etiological organisms. Keywords: Sepsis, Pediatric intensive care unit, Pediatric oncology, Predictive factors